2013
DOI: 10.1002/aic.14029
|View full text |Cite
|
Sign up to set email alerts
|

CFD simulations of turbulent fluid flow and dust dispersion in the 20 liter explosion vessel

Abstract: A CFD model was developed with the aim at simulating the turbulent flow field induced by dust feeding and dispersion within the 20 L bomb, and the associated effects on the distribution of dust concentration. The model was validated considering a set of data (pressure time histories and root mean square velocity) available in the literature. The time sequences of velocity vector and kinetic energy maps have shown that multiple turbulent vortex structures are established within the sphere. These vortices genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 21 publications
(29 reference statements)
2
33
1
Order By: Relevance
“…Finally, Di Benedetto et al 108) accomplished a CFD study to simulate the dust dispersion in the 20-liter explosion vessel. The dust concentration variation in time and space after its injection into this vessel, being the standard test equipment used by many, is still unknown.…”
Section: Modeling the Propagation Of Particulate Explosions Using Commentioning
confidence: 99%
“…Finally, Di Benedetto et al 108) accomplished a CFD study to simulate the dust dispersion in the 20-liter explosion vessel. The dust concentration variation in time and space after its injection into this vessel, being the standard test equipment used by many, is still unknown.…”
Section: Modeling the Propagation Of Particulate Explosions Using Commentioning
confidence: 99%
“…In all cases, the velocity vectors exhibit an asymmetric distribution. The asymmetric behavior has to be addressed to the effect of the particle sedimentation on the fluid flow, as also suggested by Kartushinsky et al [16] and as also shown in our previous paper [9].…”
Section: Velocity Vector and Turbulent Kinetic Energy Mapsmentioning
confidence: 92%
“…The turbulence decay starts few milliseconds after the opening of the valve -well before the end of the feeding phase -due to the decrease of the pressure gradient and the related source term ( સ×સ୮ మ ) in the vorticity equation [4,9].…”
Section: Numericsmentioning
confidence: 99%
See 2 more Smart Citations